2017
DOI: 10.1177/0284185117730102
|View full text |Cite
|
Sign up to set email alerts
|

Freehand 3T MR-guided vacuum-assisted breast biopsy (VAB): a five-year experience

Abstract: Background Magnetic resonance (MR) permits the detection of some malignant lesions that cannot be identified with mammography or ultrasonography. The characterization of these MR-only detectable lesions often requires a biopsy. Purpose To evaluate the technique, the feasibility and the accuracy of freehand 3T MR-guided VAB for the characterization of suspicious, MR-only detectable lesions and to compare VAB results with surgical pathology and follow-up imaging results. Material and Methods During 2010-2015, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…In our study, we reported lower UR than that reported in literature: 10 % of our total cases, compared to 25 % obtained by Verheyden et al [ 55 ] and 23 % by Dratwa et al [ 20 ]. In our series, 38 % of cases were classified as B3 lesions, compared to 50 % observed by Crystal et al [ 54 ] and 29 % by Gristina et al [ 18 ]. These discrepancies are partly justified by the fact that, according to Schrading [ 34 ], we have collected larger amounts of tissue for each procedure, allowing successful sampling, thus improving the diagnostic yield.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In our study, we reported lower UR than that reported in literature: 10 % of our total cases, compared to 25 % obtained by Verheyden et al [ 55 ] and 23 % by Dratwa et al [ 20 ]. In our series, 38 % of cases were classified as B3 lesions, compared to 50 % observed by Crystal et al [ 54 ] and 29 % by Gristina et al [ 18 ]. These discrepancies are partly justified by the fact that, according to Schrading [ 34 ], we have collected larger amounts of tissue for each procedure, allowing successful sampling, thus improving the diagnostic yield.…”
Section: Discussioncontrasting
confidence: 56%
“…The majority of MRgVABB procedures that have been reported in existing studies were performed with automated guided techniques designated software programs and medical devices [ 17 , 31 ]. A freehand VABB approach has been described in few other studies in the literature [ 18 , 32 , 33 ]. Freehand technique is more accessible and less expensive than automated techniques as it does not require any specifically designed software, hardware and medical devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations